2004
DOI: 10.1002/ijc.20480
|View full text |Cite
|
Sign up to set email alerts
|

Type‐specific associations of human papillomavirus load with risk of developing cervical carcinoma in situ

Abstract: We have previously shown that high human papillomavirus (HPV) 16 load in Papanicolaou smears negative for dysplasia is strongly associated with risk for carcinoma in situ (CIS) of the cervix. Here we study the amount of HPV DNA for some of the most frequent high-risk HPV types as determinants of progression to cervical CIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
91
2
8

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 38 publications
14
91
2
8
Order By: Relevance
“…For HPV 18/45, a significant OR was only seen for the highest viral-load percentile. The relationship between OR of invasive cancer and viral load of HPV 16 is similar to that previously described for CIS (Moberg et al, 2004) (Figure 1); consistent with this, CIS and invasive cervical cancer reflect the same basic aetiology. Thus, our results show that a high viral load in PAP smears is a risk factor not only for the development of CIS but also for invasive cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For HPV 18/45, a significant OR was only seen for the highest viral-load percentile. The relationship between OR of invasive cancer and viral load of HPV 16 is similar to that previously described for CIS (Moberg et al, 2004) (Figure 1); consistent with this, CIS and invasive cervical cancer reflect the same basic aetiology. Thus, our results show that a high viral load in PAP smears is a risk factor not only for the development of CIS but also for invasive cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Viral load has been suggested as a marker of nontransient infection, and high HPV load in smears with normal cytology has been associated with the risk of developing dysplasia and carcinoma in situ (CIS) van Duin et al, 2002;Dalstein et al, 2003;Moberg et al, 2004). However, it is not known whether high viral load is also predictive of invasive cervical cancer, as past studies have pooled the outcomes of invasive cancers together with earlier stages of the disease (Lorincz et al, 2002;Sherman et al, 2002Sherman et al, , 2003Sun et al, 2002;Dalstein et al, 2003;Gravitt et al, 2003).…”
mentioning
confidence: 99%
“…1 We have previously examined the effect of HPV 18/45 and HPV 31 viral load on the risk for cervical CIS. 14 Our results showed that higher viral load of HPV 18/45 or HPV 31 increases the risk of CIS, although the risk magnitude is less than that observed for HPV 16. Therefore, it is possible that HLA alleles could influence carcinoma development by affecting viral load also for other HPV types besides HPV 16. A meta analysis demonstrated a protective effect of the DRB1*1301 and DQB1*0603 alleles against development of cervical carcinoma in 18 of 19 studies.…”
mentioning
confidence: 41%
“…In this analysis, adjustment was made for case-control status because in previous analyses the HPV 18/45 load was found to affect the risk for cervical CIS. 14 The corresponding analysis performed on HPV 31 load did not show a significant relationship between load and carrier status, possibly due to the small number of subjects in each group.…”
Section: Resultsmentioning
confidence: 88%
“…Assim, a persistência de vírus de alto risco 5 , alta carga viral 2, 6-15 , persistente alta carga viral 16,17,18 , expressão do marcador de proliferação MIB-1 19 e, finalmente, a expressão do marcador de supressão tumoral p16 INK4a 4,20,21 , estão sendo apontados como prováveis marcadores de diagnóstico de lesões escamosas de alto grau e de seu prognóstico. Vários pesquisadores defendem a idéia de que a alta carga viral de HPV de alto risco teria uma importante relação com lesões intraepiteliais escamosas e sua maior gravidade 6,7,8,10,12,15,18,22 . Outros pesquisadores enfatizam a importância da persistência da alta carga viral por longo tempo, e não simplesmente uma medida isolada, assim como só teria valor a alta carga viral do HPV tipo 16, sem considerar os demais tipos 2,3,9,13,14,16,17 .…”
unclassified